Ethical sensitivity of Finnish and Estonian teachers. Issue 2 (3rd April 2023) - Ronkainen, Rina; Kuusisto, Elina; Eisenschmidt, Eve; Tirri, Kirsi
ABSTRACT: The purpose of this study was to investigate teachers' ethical sensitivity in Finland (N = 255) and Estonia (N = 412). The survey included the quantitative Ethical Sensitivity Scale Questionnaire and a qualitative open-ended question about successful teaching. In order to capture its essential characteristics, ethical sensitivity was examined using a four-factor structure. Triangulated data indicated that Caring by connecting to others was the most essential dimension of ethical sensitivity among both Finnish and Estonian teachers. By contrast, Reading ethical issues was the lowest rated and least mentioned dimension of ethical sensitivity. Approximately 30% of teachers from both countries did not perceive ethical sensitivity to be part of successful teaching. The results indicate the need for moral education to help teachers gain a more holistic understanding of the moral nature of teaching and recognize and visualize solutions for moral dilemmas in school communities.